SPE/IADC Drilling Conference 1995
DOI: 10.2118/29397-ms
|View full text |Cite
|
Sign up to set email alerts
|

Formation Compressive Strength Estimates for Predicting Drillability and PDC Bit Selection

Abstract: Various indirect measuring techniques are presently employed for estimating formation strength, which in turn is correlated to drillability and polycrystalline diamond compact (PDC) bit selection. Formation mechanical properties derived from conventional open-hole logs in combination with a rigorous assessment of formation shear wave velocities can be used successfully to determine drillability as it pertains to bit selection. Formation drillability is best determined from unconfined compressive strength and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In practice, fundamental models are calibrated against field cases and readjusted. Many investigators (Johnston 1987;Schmitt et al 1994;Horsrud et al 1994;Horsrud 1998;Spaar et al 1995;Holt et al 1996;Claesson and Bohloli 2002;Crook et al 2002;Søreide et al 2009;Fjaer et al 2008) have, instead, used outcrop shales to calibrate borehole stability models. The present work deals with data sets for Pierre-1 shale at room temperature and at the high confining pressure present at downhole conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, fundamental models are calibrated against field cases and readjusted. Many investigators (Johnston 1987;Schmitt et al 1994;Horsrud et al 1994;Horsrud 1998;Spaar et al 1995;Holt et al 1996;Claesson and Bohloli 2002;Crook et al 2002;Søreide et al 2009;Fjaer et al 2008) have, instead, used outcrop shales to calibrate borehole stability models. The present work deals with data sets for Pierre-1 shale at room temperature and at the high confining pressure present at downhole conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This method is also used to evaluate the effect of modifying a certain type of drill bit on drilling a certain formation (Perrin et al, 1997). Compressive strength and drilling potential were empirically correlated through experiments carried out at the early 1960 s. Although compressive strength should be described as a function of lateral stress, the fact that compressive strength is increased by lateral stress can be easily described by Mohr's failure criterion (Spar et al, 1995). Studies performed by Warren (1981;1987) revealed that drilling strength can be determined for conical drill bits and used for some applications such as drilling simulation and drill bit selection.…”
Section: Drilling Potentialmentioning
confidence: 99%
“…Here equation coefficient [9,10]. Optimization and compatibility of drilling technology parameters are described and analyzed by analyzing the relation between drilling sensitive parameters as drilling pressure, rotating speed, water power and formation drillability combined with the general drilling rate equation.…”
Section: Design Of Rop Programsmentioning
confidence: 99%